Sistem Remunerasi Berbasis Kinerja Menggunakan Metode Full Time Equivalent dan Simple Additive Weighting - Intan Dzikria; Mochammad Maulana Ardan; Rendys Naja Ripando (Prosiding Seminar Nasional Teknoka, 2023)
The many activities of higher education institutions with complex business processes can, without realizing it, cause employees at higher education institutions to receive excessive workloads which can lead to decreased employee performance. One way that can encourage employee motivation and performance is by providing remuneration or rewards to people fairly, evenly and consistently with incentives commensurate with the work they have done. This research aims to use the Full Time Equivalent method to evaluate workload with the results of the load being the basis for remuneration calculations using Simple Additive Weighting. The results of this research show that workload and remuneration can be assessed objectively and help make calculations more effective and efficient. The black box testing results show that the system is in accordance with user needs, where 90% of the test data has passed the requirements test. So, users can evaluate workload and provide systematic remuneration so that they can maintain optimal performance using the system built.